Effects of different compost amendments on the abundance and composition of alkB harboring bacterial communities in a soil under industrial use contaminated with hydrocarbons - Schloter, Michael (Frontiers in Microbiology, 2014)
Alkane degrading microorganisms play an important role for bioremediation of petrogenic contaminated environments. In this study, we investigated the effects of compost addition on the diversity of alkane monooxygenase gene (alkB) harboring bacteria in oil-contaminated soil originated from an industrial zone in Celje, Slovenia, to improve our understanding about the bacterial community involved in alkane degradation and the effects of amendments. Soil without any amendments (control soil) and soil amended with compost of different maturation stages, i) 1 year and ii) 2 weeks, were incubated under controlled conditions in a microcosm experiment and sampled after 0, 6, 12 and 36 weeks of incubation. By using quantitative real-time PCR higher number of alkB genes could be detected in soil samples with compost compared to the control soil after 6, 12 and 36 weeks mainly if the less maturated compost was added. To get an insight into the composition of the alkB harboring microbial communities, we performed next generation sequencing of alkB gene fragment amplicons. Richness and diversity of alkB gene harboring prokaryotes was higher in soil mixed with compost compared to control soil after 6, 12 and 36 weeks again with stronger effects of the less maturated compost. Comparison of communities detected in different samples and time points based on principle component analysis revealed that the addition of compost in general stimulated the abundance of alkB harboring Actinobacteria during the experiment independent from the maturation stage of the compost compared to the control soils. In addition alkB harboring proteobacteria like Shewanella or Hydrocarboniphaga as well as proteobacteria of the genus Agrobacterium responded positively to the addition of compost to soil The amendment of the less maturated compost resulted in addition in a large increase of alkB harboring bacteria of the Cytophaga group (Microscilla) mainly at the early sampling time points